2013
DOI: 10.1027/1618-3169/a000196
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Distraction by Auditory Deviance Is Mediated by the Sound’s Informational Value *Li and Parmentier share the first authorship of this study.

Abstract: Sounds deviating from an otherwise repetitive background in some task-irrelevant respect (deviant sounds among standard sounds) capture attention in an obligatory fashion and result in behavioral distraction in an ongoing task. Traditionally, such distraction has been considered as the ineluctable consequence of the deviant sound's low probability of occurrence relative to that of the standard. Recent evidence from a cross-modal oddball task challenged this idea by showing that deviant sounds only yield distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 63 publications
5
50
1
Order By: Relevance
“…Similar results were found in auditory-visual paradigms in which targets were visual stimuli (e. g. odd or even numbers) and the distractors were sounds (Escera et al, 1998(Escera et al, , 2000(Escera et al, , 2001. Although the early studies using either auditory (Berti and Schröger, 2003;Schröger and Wolff, 1998a;Schröger and Wolff, 1998b) or auditory-visual (Escera et al, 1998(Escera et al, , 2000(Escera et al, , 2001 paradigms consistently found prolonged response times (RTs) and decreased accuracy, recent studies found abolished or even reversed behavioral effects (Li et al, 2013;Parmentier et al, 2010;SanMiguel, et al, 2010a;2010b;Wetzel et al, 2012). These studies suggest that alerting and fore-period effects differ between standards and deviants, and these differences influence the behavioral results.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar results were found in auditory-visual paradigms in which targets were visual stimuli (e. g. odd or even numbers) and the distractors were sounds (Escera et al, 1998(Escera et al, , 2000(Escera et al, , 2001. Although the early studies using either auditory (Berti and Schröger, 2003;Schröger and Wolff, 1998a;Schröger and Wolff, 1998b) or auditory-visual (Escera et al, 1998(Escera et al, , 2000(Escera et al, , 2001 paradigms consistently found prolonged response times (RTs) and decreased accuracy, recent studies found abolished or even reversed behavioral effects (Li et al, 2013;Parmentier et al, 2010;SanMiguel, et al, 2010a;2010b;Wetzel et al, 2012). These studies suggest that alerting and fore-period effects differ between standards and deviants, and these differences influence the behavioral results.…”
Section: Introductionsupporting
confidence: 57%
“…Although at first sight, the absence of distraction-related behavioral effects may seem to contradict the assumption that distraction had happened, it has to be kept in mind that behavioral responses in such paradigms are influenced by a number of factors (for example, differences in stimulus-triggered arousal level changes), which, in sum, may lead to reduced, but also to enhanced performance in a given paradigm (Li et al, 2013;Parmentier et al, 2010;SanMiguel et al, 2010aSanMiguel et al, , 2010bWetzel et al, 2012). It is also possible that the lack of a significant behavioral distraction-effect is partially due to the "natural" stimulus-response mapping (congruent stimulusand response side), which may allow for a faster response, and less interference than in studies with arbitrary mappings (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas initial studies also showed that discrimination performance was lower and reaction times were delayed in deviant in comparison to standard trials (Schröger & Wolff, 1998b;Schröger, Giard, Wolff, 2000), recent studies suggest that reaction times sum a number of effects unrelated to distraction per se (e.g. when the task does not engage participants sufficiently, distracters may substantially increase the level of arousal, or may allow participants to prepare more efficiently for the forthcoming task-relevant event), which may even result in performance enhancement in certain paradigms (Parmentier, Elsley, Ljungberg, 2010;SanMiguel et al, 2010aSanMiguel et al, , 2010bWetzel, Widmann, Schröger, 2012;Ljungberg, Parmentier, Leiva, & Vega, 2012;Li, Parmentier, & Zhang, 2013;Wetzel, Schröger, & Widmann, in press).A series of studies administering variations of the auditory distraction paradigm showed that visual cues signaling forthcoming, potentially distracting auditory events lead to the reduction of behavioral and event-related potential (ERP) correlates of distraction (Sussman, Winkler, Schröger, 2003;Wetzel & Schröger, 2007;Wetzel, Widmann, & Schröger, 2009;Horváth, 5 Sussman, Winkler, Schröger, 2011;Horváth & Bendixen, 2012). Although the results are compatible with the interpretation that distraction is prevented because participants actively counteract distraction on the basis of information provided by the cues, other explanations are also possible.…”
Section: Introductionmentioning
confidence: 99%
“…The behavioral results basically fit into the literature using either discrete (e. g. Li, Parmentier and Zhang, 2013;Parmentier, 2014;Parmentier, Elsley and Ljungberg, 2010;Wetzel, Widmann and Schröger, 2012) or continuous (Horváth, 2014a;Horváth and Winkler, 2010) stimulation. In studies where temporal intervals between task-irrelevant and task-relevant events (in audio-visual paradigms: distracter tone onset and offset and the onset of visual target stimuli) were manipulated, the fixed foreperiod between rare distracters and targets had the potential to enhance behavioral performance (e. g. reduced reaction times or at least reduced distraction effect) on a second, task-relevant event in a 2-choice task, even though the task-irrelevant first event did not provide any specific information on the type of the succeeding second one (Holender and Bertelson, 1975;Parmentier, Elsley and Ljungberg, 2010;Wetzel, Widmann and Schröger, 2012, but see Li, Parmentier and Zhang, 2013), and implicit timing expectationsimproved reaction times and accuracy as well (Rimmele, Jolsvai and Sussmann, 2011).…”
Section:  Discussionmentioning
confidence: 48%
“…In some arrangements, task-irrelevant events cannot be disregarded at all: in a duration discrimination task (Schröger and Wolff, 1998b) the stimulus onset is a crucial reference point, and therefore even small deviations -for example, otherwise hardly noticeable (1%) pitch changes -occurring at the onset result in robust distraction effects (Berti, Roeber and Schröger, 2004). Recent behavioral studies, in which the separation of task-relevant andirrelevant events was manipulated, as well as whether the irrelevant event was followed by a relevant one on each trial, showed that the distraction-related response time delay was reduced when the foreperiod was not constant and the irrelevant event was unreliable (50% or less) in signaling the forthcoming task-relevant event (Berti, 2013;Jankowiak and Berti, 2007;Li, Parmentier and Zhang, 2013;Parmentier, 2014;Parmentier, Elsley and Ljungberg, 2010;Wetzel, Widmann and Schröger, 2012). These results suggest that in distraction paradigms, participants actually use the "task-irrelevant" events as temporal cues to enhance their task performance, that is, these events are not disregarded at all, but are incorporated in the task-behavior of the participants.…”
Section:  Introductionmentioning
confidence: 99%